A cell impedance measurement device for the cytotoxicity assay dependent on the velocity of supplied toxic fluid. (20th February 2018) - Kang, Yoon-Tae; Kim, Min-Ji; Cho, Young-Ho
Abstract: We present a cell impedance measurement chip capable of characterizing the toxic response of cells depending on the velocity of the supplied toxic fluid. Previous impedance-based devices using a single open-top chamber have been limited to maintaining a constant supply velocity, and devices with a single closed-top chamber present difficulties in simultaneous cytotoxicity assay for varying levels of supply velocities. The present device, capable of generating constant and multiple levels of toxic fluid velocity simultaneously within a single stepwise microchannel, performs a cytotoxicity assay dependent on toxic fluid velocity, in order to find the effective velocity of toxic fluid to cells for maximizing the cytotoxic effect. We analyze the cellular toxic response of 5% ethanol media supplied to cancer cells within a toxic fluid velocity range of 0–8.3 mm s −1 . We observe the velocity-dependent cell detachment rate, impedance, and death rate. We find that the cell detachment rate decreased suddenly to 2.4% at a velocity of 4.4 mm s −1, and that the change rates of cell resistance and cell capacitance showed steep decreases to 8% and 41%, respectively, at a velocity of 5.7 mm s −1 . The cell death rate and impedance fell steeply to 32% at a velocity of 5.7 mm s −1 . We conclude that: (1) the present device is useful in deciding on the toxic fluid velocity effective to cytotoxicity assay, since the cellular toxic response is dependent on the velocity of toxic fluid, and; (2) the cell impedance analysis facilitates a finer cellular response analysis, showing better correlation with the cell death rate, compared to conventional visual observation. The present device, capable of performing the combinational analysis of toxic fluid velocity and cell impedance, has potential for application to the fine cellular toxicity assay of drugs with proper toxic fluid velocity.